AMICO galaxy clusters in KiDS-DR3: weak lensing mass calibration. Issue 2 (16th January 2019) - Bellagamba, Fabio; Sereno, Mauro; Roncarelli, Mauro; Maturi, Matteo; Radovich, Mario; Bardelli, Sandro; Puddu, Emanuella; Moscardini, Lauro; Getman, Fedor; Hildebrandt, Hendrik; Napolitano, Nicola
Abstract: We present the mass calibration for galaxy clusters detected with the AMICO code in KiDS DR3 data. The cluster sample comprises 7000 objects and covers the redshift range 0.1 <z < 0.6. We perform a weak lensing stacked analysis by binning the clusters according to redshift and two different mass proxies provided by AMICO, namely the amplitude A (measure of galaxy abundance through an optimal filter) and the richness λ* (sum of membership probabilities in a consistent radial and magnitude range across redshift). For each bin, we model the data as a truncated NFW profile plus a two-halo term, taking into account uncertainties related to concentration and miscentring. From the retrieved estimates of the mean halo masses, we construct the A – M 200 and the λ*– M 200 relations. The relations extend over more than 1 order of magnitude in mass, down toM_200 2 (5) × 10^13 M_ h^-1 atz = 0.2 (0.5), with small evolution in redshift. The logarithmic slope is 2.0 for the A –mass relation, and 1.7 for the λ*–mass relation, consistent with previous estimations on mock catalogues and coherent with the different nature of the two observables.